Multi-epoch X-ray imaging of globular cluster M62 with Chandra. Issue 1 (17th August 2020) - Oh, Kwangmin; Hui, C Y; Li, K L; Kong, A K H
ABSTRACT: Using archival spectral-imaging data with a total exposure of ∼144 ks obtained by Chandra, 43 X-ray sources are detected within the half-light radius of globular cluster M62 (NGC 6266). Based on the X-ray colour–luminosity diagram or the positional coincidences with known sources, we have classified these sources into different groups of compact binaries including cataclysmic variable (CV), quiescent low-mass X-ray binary (qLMXB), millisecond pulsar, and black hole (BH). Candidates of the X-ray counterparts of 12 CVs, 4 qLMXBs, 2 MSPs, and 1 BH are identified in our analysis. The data used in our analysis consist of two frames separated by 12 yr, which enable us to search for the long-term variability as well as the short-term X-ray flux variability within each observation window. Evidence for the short-term variability and long-term variability have been found in 7 and 12 sources, respectively. For a number of bright sources with X-ray luminosities Lx ≳ 10 32  erg s −1, we have characterized their spectral properties in further details. By comparing the X-ray population in M62 with those in several other prototypical globular clusters, we found the proportion of bright sources is larger in M62 that can possibly be a result of their active dynamical formation processes.